Penyebab Kehampaan Gabah pada Persilangan Padi antar Subspesies - Hermanasari, Rini; Aswidinnoor, Hajrial; Trikoesoemaningtyas, ,; Suwarno, , (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2008)
ABSTRACTThe objective of the research was to study the factors effecting unfilled grains in intersubspecific hybridization. The research was conducted at Muara, Bogor from April 2005 to February 2006. The materials used in the research were ten F1 hybrid combinations. The evaluation was done by crossing the hybrids to Ciherang and it was resiprocal. A randomized block design with three replications were arranged in greenhouse. The results showed that five cross combinations produced higher unfilled grains and lower pollen fertility due to defective male gamets. The cross combinations that is Akitakomaci/IR64, Akitakomaci/Wayrarem, Akitakomaci/Salumpikit, Akitakomaci/Ketupat, and Akitakomaci/Kewal. Another five cross combinations produced normal pollen fertility but high unfilled grains. The high unfilled grains of four cross combinations was due to defective female gamets. The cross combination that is IR64/Sirendah Pulen, IR64/Lampung Putih, IR64/Lampung Kuning, and IR64/Mesir. The other cross combination was due to defective male and female gamets namely IR64/Brentel. Key words: Unfilled grain, F1 hybrids, male gamets, female gamets